An adaptive range–free localisation protocol in wireless sensor networks. (20th March 2014) - Gui, Linqing; Val, Thierry; Wei, Anne; Taktak, Sami
It is well known that localisation is a fundamental issue for many wireless network applications. Without the need of additional ranging devices, the range–free localisation technology is a cost–effective solution for low–cost indoor and outdoor wireless sensor networks. However, we noted that most existing algorithms were only studied using tools like MATLAB neglecting possible problems in a real wireless network context such as frame collision and node synchronisation. Thus, we propose an adaptive range–free localisation protocol (ALP) based on IEEE 802.15.4 standard, which can evaluate localisation algorithms. Using our localisation protocol, we investigate and compare the performance of our new approach to some existing range–free algorithms in terms of localisation accuracy, mobility, synchronisation and overhead. Our results show that our Mid–perpendicular, Checkout DV–hop and Selective 3–Anchor DV–hop algorithms support robust and dynamic localisation in the context of our adaptive localisation protocol.